EVALUATION OF CYTOTOXIC ACTIVITY OF CANAGLIFLOZIN IN HEPG2 CELL LINES - Mariana Amer; Shandana Altaf; Muhammad Rehman; Aniqa Atta (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This study examines the cytotoxic effects of Canagliflozin on HepG2 cell lines, serving as models for hepatocellular carcinoma (HCC). Canagliflozin was purchased in powder form from CCL pharmaceuticals. HepG2 cells were cultured in DMEM medium and plated in 96-well plates, where Canagliflozin was administered at various concentrations. Cell viability was assessed using crystal violet staining, and the half-maximal inhibitory concentration (IC50) was determined computationally. Results showed moderate cytotoxicity of Canagliflozin, with an IC50 value of 111 µM. The study highlights the potential of Canagliflozin as an anticancer agent and the need for further research to understand its mechanism and optimize therapeutic potential. Overall, this study contributes to the growing evidence supporting the use of Canagliflozin for cancer treatment.